Assessing e-commerce productivity for French micro firms using propensity score matching - Fadila Ouaida; Samer El Hajjar (Kiel Institute for the World Economy (IfW), 2018)
The benefits of e-commerce are apparent not only for small and medium enterprises (SMEs) and large firms, but also for micro firms. Hence, implementing e-sales for micro firms is worth exploring. This study examines the relationship between the use of e-commerce and productivity implications on micro firms in France using Propensity Score Matching (PSM) for the year 2012. Data used in the analysis is based on community survey "ICT & e-commerce" for micro firms. The main objective of using PSM is to assess productivity between, on the one hand, e-selling micro firms and, on the other hand, the non e-selling micro firms. The empirical results show that e-selling micro firms are more productive and have a higher turnover in 2012.
Keywords: L81; O30; 330; ICT; E-commerce; micro firms; productivity; Propensity Score Matching